1991
DOI: 10.1002/1097-0142(19910615)67:12<2984::aid-cncr2820671208>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Activity of doxorubicin and cisplatin combination chemotherapy in patients with diffuse malignant pleural mesothelioma. An italian lung cancer task force (FONICAP) phase II study

Abstract: Since DMPM has a long latency period, the overall DMPM incidence is still increasing despite recent legis-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Median survival times of patients treated with cisplatin and doxorubicin ranged from 8.8 to 15 months [15][16][17][18][19][20][21], with median survival of more than 1 year in only three studies [16,18,21] (Table 4). So, the median survival time of our patients treated with cisplatin and epirubicin appears at least equivalent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Median survival times of patients treated with cisplatin and doxorubicin ranged from 8.8 to 15 months [15][16][17][18][19][20][21], with median survival of more than 1 year in only three studies [16,18,21] (Table 4). So, the median survival time of our patients treated with cisplatin and epirubicin appears at least equivalent.…”
Section: Discussionmentioning
confidence: 99%
“…We could compare the toxicity profile of cisplatin-doxorubicin containing regimens [15][16][17][18][19][20][21] with that of cisplatin plus epirubicin (Table 4), allowing some indirect assessment of quality of life. This analysis was limited by missing data in the articles previously published.…”
Section: Discussionmentioning
confidence: 99%
“…Initially encouraging response rates experienced with the doxorubicincisplatin combination in two phase II studies carried out in Germany (RR: 46%) and Italy (RR: 25%) (Henss et al, 1988;Ardizzoni et al, 1991) failed to be confirmed by a subsequent, randomised CALGB study of doxorubicin -cisplatin vs mitomycin -cisplatin treatment (Chahinian et al, 1993). The doxorubicin-cisplatin doublet was only able to produce a 14% response rate and proved inferior to the mitomycin -cisplatin combination (RR: 26%).…”
Section: Combination Chemotherapymentioning
confidence: 99%
“…Some combination regimens have been reported as inducing higher response rates in small phase II trials. Among the combination chemotherapy regimens, doxorubicin-cisplatin doublets have been the most used drugs in phase II studies [32,33]. Most recently, oxaliplatincontaining combinations have shown activity in phase II studies: the ORR was 20% in the oxaliplatin and raltitrexed combination [34], 23% in the oxaliplatin and vinorelbine combination [35] and 40% in the oxaliplatin and gemcitabine combination [36].…”
Section: Discussionmentioning
confidence: 99%